Westphalian System of International Relations: Formation Dynamics and Disintegration Factors - I. A. Kunina (Научный диалог)
This article explores the formation and evolution of the system of international relations, asserting that the principles established by the Peace of Westphalia in 1648, which marked the conclusion of the Thirty Years’ War, fundamentally transformed inter-state relations and laid the groundwork for the entire framework of international relations. The author conducts a comprehensive analysis of the core principles of the Westphalian system, identifying criteria and universal indicators of traditional state-centric international relations within this model. The study emphasizes the significance of examining the transformative processes within international relations, tracing subsequent variations from a state-centric to an institutionally-political framework. Each reconfiguration of the Westphalian system is described with attention to its temporal and spatial characteristics. The driving forces behind the genesis and functioning of all models of traditional inter-state relations are delineated. Furthermore, the research investigates the primary causes behind the disintegration of the Westphalian system, highlighting critical international political conditions that facilitate restructuring and the emergence of new systems. The author concludes that the system of international relations is transitioning into a qualitatively distinct phase, diverging from the traditional state-centric paradigm.